Abrogation of CC Chemokine Receptor 9 Ameliorates Ventricular Electrical Remodeling in Mice After Myocardial Infarction - Huang, Yan; Ding, Hua-Sheng; Song, Tao; Chen, Yu-Ting; Wang, Teng; Tang, Yan-Hong; Barajas-Martinez, Hector; Huang, Cong-Xin; Hu, Dan (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Myocardial infarction (MI) triggers structural and electrical remodeling. CC chemokine receptor 9 (CCR9) mediates chemotaxis of inﬂammatory cells in MI. In our previous study, CCR9 knockout has been found to improve structural remodeling after MI. Here, we further investigate the potential influence of CCR9 on electrical remodeling following MI in order to explore potential new measures to improve the prognosis of MI. Methods and Results: Mice were used and divided into four groups: CCR9+/+/Sham, CCR9-/-/Sham, CCR9+/+/MI, CCR9-/-/MI. Animals were used at 1 week after MI surgery. Cardiomyocytes in the infracted border zone were acutely dissociated and the whole-cell patch clamp was used to record action potential duration (APD), L-type calcium current (ICa,L) and transient outward potassium current (Ito). Calcium transient and sarcoplasmic reticulum (SR) calcium content under stimulation of Caffeine were measured in isolated cardiomyocytes by confocal microscopy. Multielectrode array (MEA) was used to measure the conduction of the left ventricle. The western-blot was performed for the expression level of connexin 43. We observed prolonged APD90, increased ICa,L and decreased Ito following MI, while CCR9 knockout attenuated these changes (APD90: 50.57±6.51 ms in CCR9-/-/MI vs. 76.53±5.98 ms in CCR9+/+/MI, p<0.05; ICa,L: -13.15±0.86 pA/pF in CCR9-/-/MI group vs. -17.05±1.11 pA/pF in CCR9+/+/MI, p<0.05; Ito: 4.01±0.17 pA/pF in CCR9-/-/MI group vs. 2.71±0.16 pA/pF in CCR9+/+/MI, p<0.05). The confocal microscopy results revealed CCR9 knockout reversed the calcium transient and calcium content reduction in sarcoplasmic reticulum following MI. MEA measurements showed improved conduction velocity in CCR9-/-/MI mice (290.1±34.47 cm/s in CCR9-/-/MI group vs. 113.2±14.4 cm/s in CCR9+/+/MI group, p<0.01). Western-blot results suggested connexin 43 expression was lowered after MI while CCR9 knockout improved its expression. Conclusion: This study shows CCR9 knockout prevents the electrical remodeling by normalizing ion currents, calcium homeostasis, and the gap junction to maintain APD and the conduction function. It suggests CCR9 is a promising therapeutic target for MI-induced arrhythmia, which warrants further investigation.